Einschätzung der Risikobelastung in Familien im Rahmen von Frühen Hilfen: die Heidelberger Belastungsskala (HBS) und ihre Gütekriterien - Sidor, Anna; Eickhorst, Andreas; Stasch, Michael; Cierpka, Manfred (Praxis der Kinderpsychologie und Kinderpsychiatrie, 2012)
Summary Assessing Risk Exposure in Families Within the Scope of Early Intervention: The Heidelberg Stress Scale (HBS) and its Quality Criteria The aim of the study presented is to introduce the newly developed instrument to assess stress, the Heidelberg Stress Scale (Heidelberger Belastungsskala - HBS), and to examine its psychometric characteristics. The HBS was developed for a low-threshold and multi-professional assessment of a family’s stresses and resources after the birth of a child. The HBS can be used in the outreach work of family midwives, for instance, as well as in research. The validity of the HBS was tested in a sample of 284 psychosocially stressed families after the birth of their child; the inter-rater reliability was tested in a sample of 41 families that were also in stress. The HBS exhibits an excellent inter-rater reliability within a homogeneous professional group (psychology students). As relates to the construct validity, a strong positive connection between the HBS and Kindler’s screening sheet was found; the HBS exhibits a negative correlation with maternal sensitivity and a positive correlation with maternal stress level. With a high level of stress in the HBS, the risk of taking the child into care is increased by 4.5 times; the sensitivity amounts to 63.6 %. The quality criteria are satisfactory.